Age-related trajectories of quality of life in community dwelling older adults: findings from the Survey of Health, Aging and Retirement in Europe (SHARE) - Mendorf, Sarah; Heimrich, Konstantin G.; Mühlhammer, Hannah M.; Prell, Tino; Schönenberg, Aline (Frontiers in Aging Neuroscience, 2025)
IntroductionPrevious longitudinal studies have identified numerous factors influencing quality of life (QoL) in people of older age (PoA). However, most of these studies focus on group-level trends and fail to consider individual QoL trajectories or age-specific patterns over time.MethodsWe investigated longitudinal changes in QoL among community-dwelling older adults using five waves (2010–2019) of the Survey of Health, Aging and Retirement in Europe (easySHARE). Clinically relevant changes were defined via the minimal clinically important difference (MCID). We applied linear regression and linear mixed models (LMM) to explore predictors of QoL trajectories.ResultsDescriptive analyses showed that 2481 PoA (19.7%) experienced stable QoL between waves, based on changes below the MCID threshold of 3.18 points. The remaining participants exhibited consistent improvements or declines, with 1,701 different longitudinal patterns of QoL identified across the five time points. These individual patterns were further examined using LMM. LMM showed that the random effect of ID had the strongest impact on QoL across the five waves, suggesting highly individual QoL patterns. The influence of age was less significant compared to ID and decreased significantly after the addition of covariates.ConclusionOur findings underscore the importance of individual-level analyses in aging research. While QoL may appear stable at the group level, individual trajectories vary considerably. This has important implications for the use of QoL as a primary endpoint in clinical trials, particularly in geriatric populations. Notably, age alone did not significantly influence QoL over time.